Studi Komparatif Hukum Positif dan Hukum Islam Terhadap Hybrid Contract Pada Bank Syariah - Syawie, Afifah (UIN Sunan Kalijaga Yogyakarta, 2022)
This study discusses the comparative study of positive law and Islamic law on hybrid contracts in Islamic banks. The main problem is reviewing Positive and Islamic Laws on Hybrid Contracts in Islamic Banks. This article is a research library (Library Research). The data source for this article comes from the journals and books relevant to this discussion. The results of the research of this article indicate that a Multi contract or joint contract, or Hybrid Contract (al-'Uqud al-Murakkabah) is the application of two or more contracts in one transaction as a single transaction that is inseparable from each other. Sharia Bank is a Bank based on Islamic law, based on the Qur'an and Hadith. All products and services offered must not conflict with the contents of the Qur'an and Hadith. Hybrid contracts originate from a contract and develop and change. As a development, the hybrid contract has fulfilled the requirements for forming a contract with the elements and pillars of a hybrid contract similar to the elements and pillars of a Sharia contract. The hybrid contract element in Islamic banking follows the principles of contract and the provisions of Islamic law and is allowed in Islamic banking.